Examination of the tissue ghrelin expression of rats with diet-induced obesity using radioimmunoassay and immunohistochemical methods - Aydin, Suleyman; Sahin, Ibrahim; Ozkan, Yusuf; Dag, Ersel; Gunay, Ahmet; Guzel, Saadet Pilten; Ozercan, Mehmet Resat (Springer, 2012)
Currently, obesity is an important health problem in all countries, both developed and developing. Dietary habits and neurohormonal imbalances play a critical role in obesity. Circulating amounts of ghrelin, which is a neurohormonal hormone, decrease with obesity and increase with weight loss. Although it is known that both mRNA and peptide version of the ghrelin hormone are expressed in almost all tissues of both humans and animals, it is not known how obesity changes the expression of this hormone in the tissues, with the exception of the gastrointestinal system tissues. Therefore, the objective of the present study is to show how diet-induced obesity in rats changes ghrelin expression in all system tissues, and thus, to shed light on the etiopathology of obesity. The study included 12 male and 12 female 2-month-old Wistar albino species rats. The animals in the control group were fed on standard rat pellet, while those in the experiment group were fed ad libitum on a cafeteria-style diet for 2 months. When their body mass index reached 1 g/cm(2), diet-induced obese (DIO) rats were sacrificed in a sterile environment after one night fasting. Ghrelin localizations in the tissues were studied immunohistochemically using avidin-biotin-peroxidase complex (ABC) method, while tissue ghrelin amounts were analyzed using radioimmunoassay (RIA) method. When the ghrelin amounts in the urogenital system (with the exception of kidney tissues), sensory organs, respiratory system, immune system, skeletal muscle system, cardiovascular system, nervous system, and adipose tissue of rats analyzed by RIA method were compared to those in the control group, tissue ghrelin amounts in the DIO group were found lower. Immunohistochemical findings which showed a similar fall in ghrelin concentrations in the tissues were parallel to RIA results. In addition, ghrelin was shown to be synthesized in the cardiovascular system, heart muscle cells, tails of the sperms, hair follicles, lacrimal glands, tongue, and teeth of rats for the first time in this study and ghrelin syntheses in these tissues were found to decrease in obesity. Nutritional obesity is among the most common causes of obesity and the findings we have obtained through diet-induced obesity will contribute to the illumination of the etiopathology of obesity.
Keywords: Diet-induced obesity; Immunohistochemistry; Acylated ghrelin; Desacylated ghrelin; Tissue ghrelin expressions